2016
DOI: 10.1016/j.ejpn.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and nutritional problems in neurologically impaired children

Abstract: Fax: + 44 20 7813 8382Gut Motility disorders comprise a heterogeneous group of disorders that result from disruption of the functional integrity of the intrinsic neuromusculature of the gastrointestinal (GI) tract. This intrinsic neuromusculature includes the smooth muscle layers, the intrinsic nervous system of the GI tract (enteric nervous system or ENS) and the interstitial cells of Cajal. The contribution of each of these components to function can be compromised by alterations in structure (ranging from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 123 publications
(130 reference statements)
2
72
0
4
Order By: Relevance
“…When the distribution of 21 patients in this study was examined, it was seen that the patients with neurological problems (n=15, 71.4%) were in the first place. This situation is compatible with the large series published in the world 6,7 . In a study conducted in our country, it has been reported that children with neurological diseases take the first place among the patients with PEG in the childhood age group 4 .…”
Section: Discussionsupporting
confidence: 91%
“…When the distribution of 21 patients in this study was examined, it was seen that the patients with neurological problems (n=15, 71.4%) were in the first place. This situation is compatible with the large series published in the world 6,7 . In a study conducted in our country, it has been reported that children with neurological diseases take the first place among the patients with PEG in the childhood age group 4 .…”
Section: Discussionsupporting
confidence: 91%
“…In children with swallowing dysfunction, such as that seen with intellectual disability, congenital nervous and muscular diseases, and CP, gastrostomy tube feeding is the preferred method for long-term enteral feeding since it is less obtrusive than a nasogastric tube [15,16]. Neurologically impaired children frequently experience gastro-esophageal reflux disease (GERD), which may cause recurrent chest infections and recurrent vomiting, and GERD can occur whether children are tube-fed or not [17]. Although children who are tube-fed, especially those with gastrostomy and jejunostomy tube feeding, may appear as if they do not need plaque control, they often develop GERD and are at greater risk for aspiration pneumonia due to accumulated debris and oral microorganisms [15,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Neurologically impaired children frequently experience gastro-esophageal reflux disease (GERD), which may cause recurrent chest infections and recurrent vomiting, and GERD can occur whether children are tube-fed or not [17]. Although children who are tube-fed, especially those with gastrostomy and jejunostomy tube feeding, may appear as if they do not need plaque control, they often develop GERD and are at greater risk for aspiration pneumonia due to accumulated debris and oral microorganisms [15,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrostomy is one management option to improve daily feeding regimens, long-term nutrition and medication administration [8]. It is used across a range of indications [9][10][11][12][13] but children with neurological impairments have more frequent use [6,11,12,14] including a substantial proportion who have ID [15].…”
Section: Introductionmentioning
confidence: 99%